2016
DOI: 10.4103/0022-3859.180555
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals hasten head and neck cancer risk

Abstract: Background:Free radicals such as reactive oxygen species (ROS), which induce oxidative stress, are the main contributors to head and neck carcinogenesis (HNC). The present study was conducted with the aim to assess the oxidant/antioxidant status and DNA damage analysis in head and neck cancer/control patients.Materials and Methods:This prospective study was conducted on 60 patients with biopsy-proven HNC and 17 patients of head and neck disease (HND). The total antioxidant status (TAS), total oxidant status (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…These findings are in agreement with other researches outcomes [5,8,[24][25][26][27][28]. Lowered activity of these enzymes might be explained by the depletion of antioxidant defense system following the overgeneration of free radicals [29,30]. In diabetic patients glucose autooxidation results in formation of hydrogen peroxide which inactivates SOD.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in agreement with other researches outcomes [5,8,[24][25][26][27][28]. Lowered activity of these enzymes might be explained by the depletion of antioxidant defense system following the overgeneration of free radicals [29,30]. In diabetic patients glucose autooxidation results in formation of hydrogen peroxide which inactivates SOD.…”
Section: Discussionsupporting
confidence: 91%
“…Decreased antioxidant defense with increased oxidative stress was reported in patients with oral cavity cancer [40]. According to some reports, a lowered level of antioxidant enzymes may be crucial in lesion progression and can lead to the development of oxidative stress [41,42]. Our present study revealed significantly decreased GPx and SOD activity in patients with oropharyngeal cancer with HPV/EBV coinfection in relation to a single viral infection.…”
Section: Discussionsupporting
confidence: 68%
“…In another study available in the literature performed in HNC patients, poorly and moderately-differentiated tumors were identified more frequently with lower total antioxidant status (TAS). The authors also found increased damage of DNA in cancer patients and supposed that it may be connected with insufficient antioxidant capacity and excessive ROS generation which contributes to the pathogenesis of cancer in HNC patients [42].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The total antioxidant status indicates the ability of antioxidants to scavenge free radicals. The reduced activity of SOD and GPx may further the development of the lesion, resulting in oxidative stress [28]. Non-toxic levels of ROS increase proinflammatory mediators, and enzymes of the extracellular matrix take part in the destruction of apical tissue and the formation of apical lesions [26,29].…”
Section: Discussionmentioning
confidence: 99%